Childhood adverse experiences, cognitive flexibility, and goal orientation in adolescents - Maryaum Bashir; Sana Majeed (Journal of the Pakistan Medical Association, 2023)
To investigate correlation among childhood adverse experiences, cognitive flexibility, and goal orientation in adolescents, a cross-sectional study was conducted at the Riphah International University, Lahore, Pakistan, from July 2021 to March 2022, while data was collected from students of both private and government schools/colleges of Lahore. Non-Probability Purposive Sampling was carried out to recruit the sample of 250 participants, within the age range of 15-18 years. Sample size was determined by G Power Analysis and Greens Formula by Kang H (2021). Adverse Childhood Experience Scale, Cognitive Flexibility Scale, and Achievement Goal Questionnaire were used as tools for data collection. Data was analysed in SPSS version 21, using descriptive analysis, independent sample t-test, Pearson Product Moment Correlation and Multiple Regression Analysis. Results showed significant difference among males and females, results also revealed significant correlation among childhood adverse experiences, cognitive flexibility, and goal orientation in adolescents. —Continue